From healing to witchcraft: on ritual speech and roboticization in the hospital. - Pine A; Pine, Adrienne (Culture, Medicine & Psychiatry, 2011)
Healthcare Information Technology (HIT), touted as a panacea by U.S. political actors ranging from Newt Gingrich to Barack Obama, is central to emerging forms of healthcare governance which Holmes et al.-in their critique of the institutionalization of magical thinking brought about by Orwellian techno-Newspeak-have provocatively labeled fascistic. Drawing from data collected over 3 years of working with and teaching continuing education (CE) courses for thousands of registered nurses as lead political educator for the California Nurses Association/National Nurses Organizing Committee (CNA/NNOC), I argue that HIT is an integral component of a broader technological restructuring of healthcare and thus society, both of which are part of a social discourse that is tied to a transformative system of ritual speech, with profound implications for healthcare work, patient health, and democracy.